Bidimensional Structure of the Orthorexia: Development and Initial Validation of a New Instrument - Barrada, Juan Ramón; Roncero, María (Anales de Psicología / Annals of Psychology, 2018)
Orthorexia nervosa could be conceptualized as extreme or excessive preoccupation with eating food believed to be healthy. Up to now, there is no available instrument evaluating every aspect of orthorexia with sufficient psychometric guarantees. The objective of the present study was two-fold. First, to develop and validate a new questionnaire of orthorexia –the Teruel Orthorexia Scale– and, second, to analyze the association with other psychological constructs and disorders theoretically related to orthorexia nervosa: eating disorder symptoms, obsessive-compulsive disorder symptoms, negative affect, and perfectionism. Participants were 942 mainly university students who completed a battery of online questionnaires. Starting with an initial item bank of 31 items, we proposed a bidimensional test of orthorexia. This final version, with 17 items, encompassed two related, although differentiable (r = .43), aspects of orthorexia. First, Orthorectic Efforts, which evaluates the “healthy” preoccupation with diet, which is independent of psychopathology, and even inversely associated with it. Second, Orthorectic Concerns, which assesses the negative social and emotional impact of trying to achieve a rigid way of eating. This dimension represents a pathological preoccupation with a healthy diet. This study presents a new instrument that offers promising possibilities in the study of orthorexia.